Understanding the effects of sustainable milk packaging on consumer attention by incorporating eye tracking technology - Wahl, Kathryn (School of Management Studies, 2026)
incorporating eye tracking technology Consumers encounter an abundance of visual stimuli during their shopping journey including but not limited to the tangible attributes of a product or its packaging, which collectively contributes to the overall product presentation. These elements encompass graphical components, colours, textual features, the packaging size and material. As such, the consumers' allocation of attention towards these various elements is an interesting topic to explore. This study aimed to develop of more profound insight of packaging design by examining the effects of distinct visual cues such as colour, icons and the textual elements that communicate sustainability on plant-based milk product packaging from the South African Oat Milk brand OKJA. The study aimed to see how these cues influence the consumer's visual attention, which is primarily unconscious. The responses of visual attention were measured using eye tracking technology which enables more accurate data measurements of the consumers' attention compared to the traditional methods which rely on subjective self-reporting analyses. To address the research questions and objectives, this study utilised an exploratory research approach. The research method involved four quantitative tasks, followed by the qualitative component of the study which consisted of an interview. The target set of individuals was the young adult South Africans aged between 18 and 27 years old residing in Cape Town, South Africa. A total sample of 90 respondents was acquired through convenience sampling and the University of Cape Town database. For this paper, the data that was analysed was the eye tracking metrics that were generated through Tobii Pro Labs. Tobii Pro Labs measure metrics such as Time To First Fixation (TTFF), Average Fixation Duration and Total Fixation Duration (TFD), which were analysed utilising inferential statistic techniques. Mean tests such as the Analysis Of Variance (ANOVA) and t-tests were conducted to test the hypotheses. In addition, the tests for normality and equality of variance were conducted. The results of this study have revealed valuable research insights into how various sustainable visual cues on product packaging influence visual attention. Additionally, this research sheds light to the consumers' perception of sustainability across various product packages. By utilising a local milk product package OKJA, this study addressed important gaps in research in the market landscape in South African. Consequently, the evidence suggests that the consumers' distribution of visual attention does impact their perception of sustainability on product packages to an extent.